Exploring Computer Science Student Perceptions on Service Learning: Online and On-Campus Modality Comparative Study - Wright, Sarah; Lara, Miguel (Journal of systemics, cybernetics and informatics, 2025)
This study examines computer science students' perceptions of their service learning experiences, comparing fully online and on-campus modalities. Service learning is a teaching approach that integrates community engagement with academic learning, offering students opportunities to apply technical knowledge in real-world settings while addressing community needs. An electronic mixed methods survey was developed, tested for validity and reliability, and distributed to 110 college students enrolled in both modalities of our 400-level Race, Gender, and Class in the Digital World course. About 57% of students responded to the survey: 50 on campus and 13 fully online. Using survey data, this research evaluates students' views on skill development, career preparation, and their ability to apply computer science concepts to practical challenges. Additionally, qualitative analysis of open-ended responses reveals insights into students' reflections on social responsibility, professional growth, and challenges faced during their service learning. The findings indicate minimal differences between the two modalities, suggesting that service learning offers consistent benefits regardless of how it is delivered. However, unique challenges were highlighted, including managing expectations in virtual collaborations and navigating non-technical client relationships. Implications for curriculum design, strategies to foster deeper community impact, and directions for future research are discussed, emphasizing the value of service learning in computer science education.